2022
DOI: 10.53730/ijhs.v6ns3.6774
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Pathological and demographic profile of patients of cervical tubercular lymphadenitis in hilly region of Uttarakhand

Abstract: Tuberculosis (TB) is a communicable disease that is a major cause of ill health. The hilly region of Uttarakhand has difficult terrain and is one of the least accessible regions of the country. This present study was to evaluate the Clinico-pathological and demographic profile of patients of cervical tubercular lymphadenitis in hilly region of Uttarakhand, India. Detailed History and physical examination was to done and all previous investigations were compiled. Routine investigations like HIV, RBS and Chest X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The demographic profiles of this study were consistent with studies of Southeast Asian regions, where most of the subjects were from rural areas. [11][12][13] The right cervical lymph node was the most common predilection in our study (46%), a consistent survey of Kamal et al, 14 but much higher in north India (67.8%). Gautam et al 15 study found that cervical lymph nodes are the most common site of tuberculous lymphadenopathy in 60%-90% of cases.…”
Section: Discussionsupporting
confidence: 88%
“…The demographic profiles of this study were consistent with studies of Southeast Asian regions, where most of the subjects were from rural areas. [11][12][13] The right cervical lymph node was the most common predilection in our study (46%), a consistent survey of Kamal et al, 14 but much higher in north India (67.8%). Gautam et al 15 study found that cervical lymph nodes are the most common site of tuberculous lymphadenopathy in 60%-90% of cases.…”
Section: Discussionsupporting
confidence: 88%